Pulmonary cavitary lesions may be one of the presenting features in Ig A nephropathy - B. Isci (Reumatismo, 2018)
Immunoglobulin A (Ig A) nephropathy is the most frequent primary glomerulonephritis. Renal limited disease is the most widespread clinical form of the disease. Pulmonary involvement may also be seen concomitantly and capillaritis with pulmonary hemorrhage is the most frequent pulmonary involvement. In this paper, for the first time in literature, we describe an Ig A nephropathy patient with multiple pulmonary cavities as one of the presenting features of the disease. Also, no other etiology for the cavities was found other than Ig A nephropathy. Herein, possible pathogenesis might be capillaritis or deposition of immune complexes. As a result, it should be kept in mind that pulmonary cavity may be the presenting feature of Ig A nephropathy especially with other frequent signs of the disease.